Challenges of political communication with young people on social media - A. A. Komarova (Вестник университета)
The article is devoted to the identification of problems in communication between modern politicians and youth and the study of effective communication between youth and opinion leaders. The information channels through which modern youth learns current political news were investigated. In the course of the study, it was important to find out not only which communication and information channels influence the formation of political opinions of modern youth, but also how young people participate in public discussion of topical issues, with the help of which online resources they broadcast their point of view. In order to create effective communication with the youth audience, including in the field of political topics, attention should be paid to how media personalities who are attractive to young people and who can shape the moods and orientations of modern young people form their content, how they communicate, how they convey information.